2022
DOI: 10.1037/aca0000377
|View full text |Cite
|
Sign up to set email alerts
|

The role of expertise in visual exploration and aesthetic judgment of residential building façades: An eye-tracking study.

Abstract: The building façade has considerable effects on the aesthetic experience of observers. However, the experience may differ depending on the observers' expertise. This study was conducted to explore the impact of expertise on preference, visual exploration, and cognitive experience during the aesthetic judgment of designed façades. For this purpose, we developed a paradigm in two separate parts: aesthetic judgment (AJ) and eye movement recording (EMR). Thirty-eight participants participated in this experiment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Architectural appearance greatly impacts the aesthetic experience of the observer, while the judgment of beauty and unattractiveness are closely related to personal expertise as well as subjective feelings. Therefore, architects usually use eye tracking technology to not only determine the aesthetic effect of architectural elements but also explore the relationship between the observer’s gaze pattern with the formal properties of architectural elements under different design parameters ( Jam et al, 2021 ). Previous studies have also reported the use of ERP and fMRI in analysis of key psychological dimensions sensitive to specific design parameters and the neural features evoked ( Ma et al, 2015 ; Coburn et al, 2020 ).…”
Section: Knowledge Fusion Of Neuroscience Tools In Building Constructionmentioning
confidence: 99%
“…Architectural appearance greatly impacts the aesthetic experience of the observer, while the judgment of beauty and unattractiveness are closely related to personal expertise as well as subjective feelings. Therefore, architects usually use eye tracking technology to not only determine the aesthetic effect of architectural elements but also explore the relationship between the observer’s gaze pattern with the formal properties of architectural elements under different design parameters ( Jam et al, 2021 ). Previous studies have also reported the use of ERP and fMRI in analysis of key psychological dimensions sensitive to specific design parameters and the neural features evoked ( Ma et al, 2015 ; Coburn et al, 2020 ).…”
Section: Knowledge Fusion Of Neuroscience Tools In Building Constructionmentioning
confidence: 99%
“…Cook et al [ 18 ] studied the influence of personality on aesthetic preferences, and indicated that architectural familiarity was found to be highly predictive of preferences for all styles. Jam et al [ 19 ] confirmed the impact of expertise on preference, visual exploration, and cognitive experience during the aesthetic judgment of designed façades. By comparing the perceptional similarities and differences between designers and users on residential buildings' facades.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, differences in the cognition of viewers have been confirmed, eye movement indicators such as the first fixation duration, the total fixation duration and the visit count can all be interpreted as target attractiveness and information coding difficulty [ 19 ]. But there is a lack of a clear definition of eye movement indicators on public perceptions such as impression and acceptance.…”
Section: Introductionmentioning
confidence: 99%